Distribution Characteristics and Formula Revision of Lightning Current Amplitude and Cumulative Probability in Zhejiang Province - Xia, Li; Nannan, Song; Yanfeng, Fan; Yinping, Liu; Qing, Liu; Xiaolin, Guan; Pei, Miao (Frontiers in Environmental Science, 2022)
The cumulative probability distribution of the lightning current amplitude can reflect the lightning activity and is important for the lightning protection engineering technology. Based on the lightning location data from 2009 to 2019, the distribution characteristics of the lightning current amplitude and cumulative probability are studied. The results show that a total of 8,634,858 lightning flashes occurred in Zhejiang province in last 11 years. Negative flashes are much more common than positive ones, accounting for 87.44% of the total. The percentage of the lightning current amplitude between 2 and 100 kA is 94.3%. The average amplitude of positive flashes is significantly higher than that of negative flashes. For the current amplitude of positive flashes, the peak occurs in March and gradually decreases with the increase of the month, reaching its lowest in December. But the monthly distribution of negative flashes is relatively concentrated, especially from February to October. When lightning current amplitude is higher than 25.5 kA, the cumulative probability of positive flashes is significantly higher than that of negative flashes and vice versa. The cumulative probability distribution of negative flashes is closer to that of total flashes and is significantly different from that of positive flashes. In order to get a more suitable cumulative probability formula of lightning current amplitude and corresponding parameters in Zhejiang province, the Levenberg–Marquardt method is used. By fitting the measured data with the formulas recommended by the Institute of Electrical and Electronics Engineers (IEEE) and Electric Power Industry Standard of China (Code for design of overvoltage protection and insulation coordination for AC electrical installations GB/T 50064-2014), respectively, the correlation coefficients of different polarities are obtained. By comparing the aforementioned two fitting results, it is found that the formula recommended by the IEEE can more objectively reflect the probability distribution characteristics in Zhejiang province, and the accuracy of the derived formula is verified by using the lightning current data in 2020. It shows that the curve based on the measured values is consistent with that fitted by the IEEE formula but quite different from that fitted by the GB/T 50064-2014 formula.